Keterbatasan International Committee of The Red Cros (ICRC) dalam Mengatasi Krisis Kemanusiaan di Suriah - Eko Nurfahmi (Journal of International and Local Studies, 2017)
The role of the International Committee of the Red Cross (ICRC) in addressing the humanitarian crisis in Syria since the conflict between the government and the rebels who disagree with the leadership of President Bashar al-Assad, the conflict that caused more hundred thousands victims lost their lives, and millions of people in Syria became refugees and IDPs (Internal Displaces Person). Prolonged conflict caught the attention of the international community to demonstrate the ICRC’s commitment in providing humanitarian assistance to the Syrian people who affected. Furthermore, it is expected to encourage the ICRC to carry out its duties and responsibilities as a humanitarian organization in Syria and instrumental help Syria overcome the problems of humanity. The ICRC as a humanitarian NGO engaged primarily in armed conflict are not able tomove freely and engage in armed conflict everywhere to make humanitarian intervention. Although ICRC’s activities have already got legal mandate and strong right in international law, this undeniable that they are struggling to face he barriers in performing their duties, especially in Syria.